Photogrammetric Bathymetry for the Canadian Arctic. Issue 1 (2nd January 2020) - Hodúl, Matúš; Chénier, René; Faucher, Marc-André; Ahola, Ryan; Knudby, Anders; Bird, Stephen
Abstract: Remote sensing is becoming common in the estimation of bathymetry for navigational charting through a process known as Satellite Derived Bathymetry (SDB). Most SDB techniques currently used by hydrographic offices employ an empirical approach, requiring the use of in-situ data to calibrate a relationship between spectral information and coincident depths. This article reports on a multi-site test of an alternative SDB method which uses photogrammetry to extract depths from stereo WorldView-2 imagery. In areas with heterogeneous seafloors, the empirical approach faces difficulties in establishing the relationship between colour and depth, while the photogrammetric approach uses the contrasting seafloor features for triangulation. Additionally, the photogrammetric method may be applied in areas lacking previous survey data. Five study areas in Nunavut, Canada were selected to test the robustness of the method in different environments and under different imaging conditions. Study areas were (with resulting RMSE/Bias given in metres) Coral Harbour (0.84/−0.47), Cambridge Bay (1.16/−0.15), Queen Maud Gulf (0.97/0.06), Arviat (0.99/−0.009), and Frobisher Bay, where extraction largely failed due to environmental conditions. Accuracies demonstrated here are similar to those seen using the empirical approach, suggesting that these two methods may be used in conjunction, each applied to regions where they are better suited.